Poland versus the EU Common Security and Defence Policy (Economic and Political Thought, 2014)
The article deals with the issue of developing Common Security andDefence Policy of the European Union in its broad sense and the role ofPoland in the area of this organisation’s extended security. Having regainedfull sovereignty as a result of the collapse of the bipolar confrontational East-West system, in the new geopolitical constellation on the European continent,Poland strove to obtain guarantees of national security from the formallyinstitutionalised Western world security structures. The accession of Poland tothe Euro-Atlantic security area, i.e. NATO (1999), and the European Union(2004) was the crowning achievement of the process. Since then, Poland hashad an opportunity to directly and actively influence the EU foreign policy,security and defensive identity. For the closest ally of the United States inEurope, the process was very difficult to implement because the biggest EUstates, Germany and France, wanted to control foreign policy of the newNATO and EU member states. The situation changed when Poland declaredclearly that it was all for supporting the European security structures. Sincethe Polish Presidency of the Council of the European Union in the second halfof 2011, Poland has consistently supported the strengthening of cooperationbetween member states within the Common Security and Defence Policy ofthe European Union with an aim of making this organisation gain a status ofthe key player in the international politics in the future.